Fenologia, produção e qualidade dos frutos de genótipos de pitangueira (eugenia uniflora l.) nas condições climáticas do semiárido - Andrade, Alex Danilo Monte de (Universidade Federal Rural do Semi-Árido, 2018)
The pitangueira (Eugenia uniflora L.) has several genotypes with high productive potential and good agronomic characteristics. The cultivation of pitangueira in the Northeast has been growing rapidly, however, most of the orchards are made up of plants originated from sexual propagation, possessing a high degree of genetic variability. The objective of this study was to study the phenological, productive and fruit quality of the different genus species of pitangueira (Eugenia uniflora L.) in the climatic conditions of the semiarid. During the experimental period, the following variables were evaluated: fruit yield (g), diameter and length (mm), percentage of seeds, percentage of pulp, soluble solids, titratable acidity, vitamin C and the ratio soluble solids/acidity. The genotypes showed variability with respect to the physical and chemical characteristics of the fruit. The genotypes A1, A2, A3, A18, A19, A20, A25, A26, A27, A28, A31, A33 and A37 were the most precocious in the climatic conditions of the semiarid, producing 39 days after production pruning. The genotypes A13, A1, A39 and A32 showed thhe highest yield and productivity in the first and second cycles (2017/2018). The fruits of the genotypes A8, A9, A11, A12, A13, A18, A25, A26, A43 and A44 had the best fruit production and quality characteristics
Keywords: Comportamento fenológico; desempenho produtivo; qualidade dos frutos; variabilidade genética; Phenological behavior; productive performance; fruit quality; genetic variability; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA